The Benefits and Risks of the Internet for ‎Students with Mental Disability as Viewed by ‎their Parents in the State of Kuwait - Al-Dhafairi, Faiez (Jordan Journal of Educational Sciences, 2023)
This study aimed at identifying the benefits and risks of the Internet for the students with mental disability as viewed from their parents in the State of Kuwait. 156 parents who were selected through the deliberate method were the subjects of this study. They were asked to respond to 24 questions on a scale that the researcher had developed; the questions were split into two main categories: the benefits and risks of the Internet. In this study, the descriptive survey method was employed. Parents of students with mental disability gave the Internet high marks for its benefits, and the study's findings also showed that there were no statistically significant differences in the average benefits of the Internet based on the student's age or gender. The study also found that parents of students with mental disability gave the Internet average ratings when it came to the risks. The results also showed that the averages of the risks of the Internet were statistically different depending on the student's gender and age. The study reported that parents of students with mental disability should know right away that the Internet can pose risks for their kids